Apresente uma derivação à extrema esquerda (DEE) da sentença a = a * (b - c) + (d / e) sobre a gramática a seguir.
G = ({A, B, C, D, E, F, G}, {a, b, c, d, e, =, +, -, *, /, (, )}, P, A)
P = {< A > -> < G > = < B >
< B > -> < D > < C > | < D >
< C > -> + < D > < C > | - < D > < C > | + < D > | - < D >
< D > -> < F > < E > | < F >
< E > -> * < F > < E > | / < F > < E > | * < F > | / < F >
< F > -> ( < B > ) | < G >
< G > -> a | b | c | d | e }
< A >
< G > = < B >
a = < B >
a = < D > < C >
a = < F > < E > < C >
a = < G > < E > < C >
a = a < E > < C >
a = a * < F > < C >
a = a * ( < B > ) < C >
a = a * ( < D > < C > ) < C >
a = a * ( < F > < C > ) < C >
a = a * ( < G > < C > ) < C >
a = a * ( b < C > ) < C >
a = a * ( b - < D > ) < C >
a = a * ( b - < F > ) < C >
a = a * ( b - < G > ) < C >
a = a * ( b - c ) < C >
a = a * ( b - c ) + < D >
a = a * ( b - c ) + < F >
a = a * ( b - c ) + ( < B > )
a = a * ( b - c ) + ( < D > )
a = a * ( b - c ) + ( < F > < E > )
a = a * ( b - c ) + ( < G > < E > )
a = a * ( b - c ) + ( d < E > )
a = a * ( b - c ) + ( d / < F > )
a = a * ( b - c ) + ( d / < G > )
a = a * ( b - c ) + ( d / e )